Implications for blinding in clinical trials with THC-containing cannabinoids based on the CANNA-TICS trial - Müller-Vahl, Kirsten R.; Jakubovski, Ewgeni; Fremer, Carolin; Lenz-Ziegenbein, Martina; Großhennig, Anika; Klages, Carolin; Koch, Armin; Haas, Martina; Pisarenko, Anna (Frontiers in Neuroscience, 2022)
Randomized double-blind placebo-controlled trials (RCTs) are regarded the gold standard for clinical trials. While there are established standards to avoid unblinding, in RCTs using tetrahydrocannabinol (THC) containing cannabinoids, however, accidental unblinding as well as intentional self-unbinding must be considered as a particular issue, since THC tests are widely available. To investigate unblinding rates in an RCT using a THC containing cannabinoid, we re-contacted participants of the CANNA-TICS trial participating in our study center in Hannover (54/97 participants). Of 54 participants, 53 could be reached. Of these, one participant (2%) stated that she had unblinded herself intentionally during the treatment phase and another three patients (6%) reported intentional unblinding after the end of treatment. Noteworthy, two patients provided discrepant information and denied self-unblinding during the interview, although during study/clinic visits they had reported having done so. Thus, based on all available information, three participants (6%) unblinded themselves intentionally during the treatment phase and another three (6%) after end of treatment. Accidental unblinding during the treatment phase was reported by 4/54 participants (7%) (during study visits). Since one participant reported both intentional self-unblinding (during the interview) and accidental unblinding (during a study visit), the total unblinding rate was 17% (n=9). Of these, seven participants (13%) reported unblinding during the treatment phase. During the interview, only 34% (n=18/53) of participants stated that they had been aware of the possibility of self-unblinding. Thus, altogether 33% (n=6/18) of those being informed about the possibility of self-unblinding did so and half of them (3/18, 17 %) during the treatment phase. It can be expected that in parallel to increasing knowledge on medicinal and recreational use of cannabinoids, more and more people will also be informed about the availability of THC tests. Hence, in future RCTs using THC containing cannabinoids, researchers have to take the possibility of accidental and intentional unblinding into consideration, when designing the study.